This research imes to determine whether dyspepsia is a serious problem for our society. The frequency of dyspepsia has been explored in different parts of the societ in Ankara - Nazmiye KOYUNCU,; Özden UZUNALİMOĞLU,; Kadir BAHAR,; Fahri IŞITIN,; Hayri KARAASLAN,; Alp TANRIVERDİ,; Aydın YAĞMURLU,; Günay ŞAHİN,; Sevil KOÇAK,; Mutlu MEYDANLI,; Ali ÖZDEN,; Emine YILMAZ,; et al. (Turkish Journal of Gastroenterology, 2020)
-